Fotoassociação caótica no oscilador de Morse - Figueira, Larissa de Oliveira [UNESP] (2014)
In this work we investigate the laser-pulse photoassociation of diatomic molecules laser from the point of view of classical mechanics, the photoassociation consists of the formation of diatomic molecule from a pair of colliding atoms by the action of external fields. This system is modeled by the driven Morse oscillator. We solve the classical equations of motion and we define a probability of photoassociation we define a photoassociation probability allowing comparisons with quantum results. Thus we investigated the chaotic behavior of the dynamics of formation of molecules with laser and analyze appropriate schemes for photoassociation by applying certain control techniques, which include pulse of pre-defined shape as well as control pulses locally determined